MENUJU SISTEM EKONOMI PANCASILA REFORMASI ATAU REVOLUSI - Mubyarto (UGM`, 2004)
intellectuals are at their best when distant from politics and power.... only when intellectuals step back from governing institutions will they be able to speak truth to pwer... Intellectuals, therefore had to conceive of themselves as cultural worker, responsible not solely for generating ideas but also for ensuring that those ideas wound up in the minds and arguments of a thoughiful audience and public. (K. Mattson, 2002: 9, 267)